2020
DOI: 10.5194/aab-63-91-2020
|View full text |Cite
|
Sign up to set email alerts
|

The effects of soy oil, poultry fat and tallow with fixed energy : protein ratio on broiler performance

Abstract: Abstract. In this study, the effects of using soy oil (SO), poultry fat (PF) and tallow (T) in broiler feed at fixed energy : protein ratio on field and slaughter parameters were evaluated. The average live weight (ALW), feed conversion ratio (FCR), production efficiency factor (PEF) and mortality were investigated as field performance parameters; carcass weight (CW), carcass yield (CY), heart–liver weight (HLW), heart–liver yield (HLY), abdominal fat weight (AFW) and abdominal fat yield (AFY) were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
4
6
0
1
Order By: Relevance
“…We also found that partial and total replacement of SO by PF in broiler diets had no significant impact on final body weight, FCR, EFEF, and carcass traits except abdominal fat, which increased PF50 and PF100. A similar trend was reported by Okur [ 31 ] and Sanz [ 32 ], who noticed an elevation in abdominal fat weight when animal fats were used in broiler diets. The growth performance of broilers is greatly influenced by dietary fat sources and their FA profiles, particularly essential FAs, such as α-linolenic acid and linoleic acid, as their deficiency may retard broilers growth [ 33 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We also found that partial and total replacement of SO by PF in broiler diets had no significant impact on final body weight, FCR, EFEF, and carcass traits except abdominal fat, which increased PF50 and PF100. A similar trend was reported by Okur [ 31 ] and Sanz [ 32 ], who noticed an elevation in abdominal fat weight when animal fats were used in broiler diets. The growth performance of broilers is greatly influenced by dietary fat sources and their FA profiles, particularly essential FAs, such as α-linolenic acid and linoleic acid, as their deficiency may retard broilers growth [ 33 ].…”
Section: Discussionsupporting
confidence: 87%
“…As our results revealed, the differences between SO and PF in these FAs were insufficient to induce significant differences in birds’ growth performance. The lack of differences in growth performance of birds fed diets with SO or PF could also be attributed to the equilibrium ratios of energy-to-protein and energy-to-amino acid in these diets [ 27 , 31 ]. Additionally, Pesti et al [ 27 ] reported that feeding on fat sources with high metabolizable energy resulted in a high amount of fat being deposited.…”
Section: Discussionmentioning
confidence: 99%
“…It contains about 45% fat (wet basis, Cliche et al., 2003 ) and about 9% proteins (wet basis, Farmani & Rostammiry, 2015 ) that make it a potential raw material for the recovery of fat and protein (or their derivatives). Chicken skin fat is composed of about 30% saturated fatty acids, 50% monounsaturated fatty acids, and about 20% polyunsaturated fatty acids (Fallah‐Delavar & Farmani, 2018 ; Naderi et al., 2016 ) and several applications, including soap production, biodiesel production (Shi et al., 2013 ), and use in animal feed formulation (Okur, 2020 ) and margarine and shortening production (Naderi et al., 2016 ), have been described for that. According to Bonifer and Froning ( 1996 ), proteins of chicken skin include 29% collagen, 10% salt‐soluble proteins, 12% water‐soluble proteins, and 49% other proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The commodity soybean oil had an oleic acid content of 21.80%, compared to 81% oleic acid within the Missouri high oleic soybean oil. Commodity soybean oil was utilized as the control in this experiment due to its use as the preferred oil source in poultry diets (Okur, 2020). Broilers received a twostage diet consisting of a starter diet (d0-21) and a grower diet (d21-42).…”
Section: Experimental Designmentioning
confidence: 99%
“…The four treatment diets consisted of two control diet corn-soy diet that included conventional soybean oil at levels of 2.5% (C2.5) and 5.0% (C5) and two corn-soy diets containing Plenish® (high oleic soybean oil) at 2.5% (P2.5) and 5.0% (P5). Commodity soybean oil was utilized as the control in this experiment to compare Plenish® to, due to its use as the preferred oil source in poultry diets (Okur, 2020). Rate of oil inclusion of 2.5% and 5% for both oils was used to observe the effect of increased rate of inclusion of Plenish® on broiler performance and fatty acid profile of broiler tissues.…”
Section: Experimental Designmentioning
confidence: 99%